The Influence of Brand Image and Price Perceptions on Purchasing Decisions Mediated by Consumer Buying Interest in Levi Strauss & Co - Arief Aulia Fahmy; Wiyadi Wiyadi; Muzakar Isa; Zulfa Irawati (Brilliant International Journal Of Management And Tourism, 2024)
This research aims to analyze the influence of brand image and price perception on purchasing decisions by considering purchasing interest. The sample for this research is FEB UMS students who wear jeans products from Levi Strauss & CO. The sampling technique used nonprobability sampling and obtained 127 respondents. Analysis of this research data uses the PLS 3.0 program. The research results state that brand image has a positive and significant influence on consumer buying interest, price perception has a positive and significant influence on consumer buying interest, brand image has a positive and significant influence on purchasing decisions, price perception has a positive and significant influence on purchasing decisions, Consumer buying interest has a positive and significant influence on purchasing decisions, consumer buying interest is able to mediate brand image on purchasing decisions, and consumer buying interest is able to mediate price perceptions on purchasing decisions.